Factors Related to the Level of Anxiety in Pulmonary Tuberculosis Patients in the City of Bandung - Vita Lucya; Helmia Amri (STIKep PPNI Jawa Barat, 2023)
Aims: This study aims to determine the influencing factors Drug anxiety in pulmonary TB patients. Methods: A quantitative descriptive design with a cross-sectional investigation on 95 patients with pulmonary tuberculosis who became respondents via total sampling was used in this study. The State Trait Anxiety Inventory (STAI) questionnaire was employed in this investigation. Frequency, Spearman correlation, and Simple Linear Regression were employed in this study's data analysis. Results: The findings of this study on anxiety factors in TB patients show that the degree of education, information, and related family support pulmonary TB patient anxiety. Conclusion: This study shows that the anxiety that appears in patients with pulmonary tuberculosis is influenced by several interrelated factors.